Empirical study of software component integration process activities. Issue 2 (1st April 2013) - Mahmood, Sajjad
Abstract : The component integration phase is key to component‐based system (CBS) success because of its profound impact on the quality of a software product. However, CBS integration is a complex phase because it is rarely the case that components are perfectly matched and ready for 'plug and play'. The component integration phase involves assembling pre‐existing software components usually developed by different parties, and writing glue‐code to handle the mismatches between CBS‐to‐be requirements and available component features. The objective of the study is to gain an in‐depth understanding of the impact of integration process activities on the overall success of a CBS. The empirical study also investigates the inter‐dependency between the CBS integration process activities. A survey was developed and data from CBS practitioners working in small‐to‐medium‐sized organisations were collected. The results show that 'component functional specification', 'structural compatibility analysis', 'architectural model development' and 'early glue‐code specification' are integration process activities that have positive correlation with the successful development of a CBS. However, the results indicate that the 'quality properties analysis' is not carried out as an integration process activity by the majority of CBS practitioners during development of a CBS. Furthermore, the results of the survey also provide empirical evidence that there is a positive association between various key CBS integration process activities.